Antenatal-Based Pilot Psychosocial Intervention to Enhance Mental Health of Pregnant Women Experiencing Domestic and Family Violence in Nepal. Issue 5 (March 2022) - Sapkota, Diksha; Baird, Kathleen; Saito, Amornrat; Rijal, Pappu; Anderson, Debra
Survivors of domestic and family violence (DFV) report poorer quality of life and worsening mental health. This study evaluated the effect of a counseling and education intervention on the mental health and help-seeking behaviors among pregnant women living with DFV. A parallel pilot randomized controlled trial was performed among 140 pregnant women attending an antenatal clinic of a tertiary hospital of Nepal. Using computer-generated random numbers, participants were randomized to the intervention group (a counseling session, an information booklet about DFV, and contact details of the counselor) or a control group (usual care plus a booklet containing contact details of local DFV support services). Outcome measures included mental health, quality of life (QOL), self-efficacy, social support, and safety planning behaviors. Analyses followed intention-to-treat, using the generalized estimating equation model. Intervention participants showed significant improvements in anxiety (β = −3.24, p < .001) and depression (β = −3.16, p < .001) at postintervention. Such improvements were also sustained at follow-up assessment ( p < .001). Significant group and time interaction for QOL, social support, use of safety behaviors, and self-efficacy ( p < .05) revealed a greater increase in these outcome measures among intervention participants at both follow-up assessments compared with the control group. This pilot integrated intervention showed promising outcomes in improving the mental health, social support, and the use of safety behaviors among women with DFV. This intervention could be incorporated into regular antenatal care as a strategy to identify and support victims of DFV. Larger controlled trials with longer follow-up are needed to support and expand on the current findings regarding the effectiveness of a psychosocial intervention targeting victims of DFV in resource-constrained settings.